Rich Pickings? Risk, Return, and Skill in Household Wealth - Bach, Laurent; Calvet, Laurent E.; Sodini, Paolo (American Economic Review, 2020)
We investigate wealth returns on an administrative panel containing the disaggregated balance sheets of Swedish residents. The expected return on household net wealth is strongly persistent, determined primarily by systematic risk, and increasing in net worth, exceeding the risk-free rate by the size of the equity premium for households in the top 0.01 percent. Idiosyncratic risk is transitory but generates substantial long-term dispersion in returns in top brackets. Systematic and idiosyncratic risk both drive the cross-sectional distribution of the geometric average return over a generation. Furthermore, wealth returns explain most of the historical increase in top wealth shares. (JEL D31, G11, G51)